Pengaruh Suhu dan Lama Pengovenan Ikan Tongkol yang direndam dalam Larutan Asap Cair Batang Bambu Tabah terhadap Karakteristik Produk Ikan Olahan - Luber Perkasa Turnip; I Wayan Widia; Pande Ketut Diah Kencana (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2020)
Tuna has a high protein and water content, and has solid meat. But tuna is also very easy to damage. The cause of damage fish is a high water content which can cause microorganisms to multiply easily. Fumigation with liquid smoke is safer and more practical than conventional fumigation, because liquid smoke contains phenol, carbonyl and organic acids which are useful for providing a distinctive taste and as preservatives in fish. The liquid smoke comes from stem of tabah bamboo (Gigantochloa nigrociliataBuse-Kurz). The purpose of this study was to determine effect of temperature and duration heating using oven in tuna which soaked liquid smoke stems tabah bamboo solution to the characteristics of processed fish products and to find out the temperature and duration heating using oven of the best organoleptic characteristics of tuna which soaked liquid smoke stems tabah bamboo solution. The method used is Factorial Completely Randomized Design with two factors. The first factor is the treatment of oven temperature which consists of three levels, and the second factor is the treatment of oven time which consists of three levels. Each treatment was repeated twice.The best combination of treatments is the oven temperature of 100⁰C, oven for 4 hours produce pH 5.5, water content 58.06%, ash content 1.69%, protein content 18.29%, color 3.94, aroma 4.28, texture 4.72, taste 4.5, and the overall acceptance 4.39